Do biobanks need pharmacists? Support of pharmacy students to biobanking of human biological material for pharmaceutical research and development - Domaradzki, Jan; Majchrowska, Anita; Cielecka-Piontek, Judyta; Walkowiak, Dariusz (Frontiers in Pharmacology, 2024)
Objectives: This study aimed to assess the biobank awareness among Polish pharmacy students and how it affects their support for biobank research. Methods: A survey among 366 pharmacy students enrolled at two Polish medical universities: the Poznań University of Medical Sciences and Medical University of Lublin was conducted. Results: Although most pharmacy students felt positivity about biobanking and expressed the willingness to donate their biospecimens for biomedical research, their awareness on research biobanks was low. Their willingness to participate was driven by the desire to benefit society, help advance science and develop new therapies. While students supported donation for most types of research, biobanks run by medical universities were the highest trusted research institutions. The primary factors associated with students willingness to participate were religiosity and place of study. Notably, nonreligious students and those studying in Poznan exhibited more favourable attitudes toward donating for research and expressed greater support for the establishment of research biobanks in Poland. Conclusions: Since biobank awareness among future pharmacists is inadequate incorporating biobank competency domains into education and training of pharmacists is required.